#### Answer

y= -0.5
x= $\frac{1}{3}$

#### Work Step by Step

step 1:
Find a common factor between one of the variables x or y. In this case we can multiply $\frac{1}{2}$ by 18 to make the x variable equal in both equations.
9x - 4y = 5
$\frac{1}{2} + \frac{1}{3}$ = 0
9x - 4y = 5
$(18) \frac{1}{2} + \frac{1}{3}$ = 0
Step 2:
X values cancels out. As y values are opposites you have to take them away.
9x - 4y = 5
9x + 6y = 0
-10y = 5
step 3:
rearrange so you get the y value on its own.
-y =$ \frac{3}{9}$
y = - $\frac{1}{2}$
Step 4:
Use your y answer to solve one of the equations by substituting y by -$\frac{1}{2}$
9x - 4 (- $\frac{1}{2}$) = 5
Step 5:
rearrange the equation so x is left by its own.
9x -4 (-0.50) = 5
9x + 2 = 5
9x = 5 -2
9x = 3
x =$ \frac{3}{9}$
x = $\frac{1}{3}$